Trip Coil Signature Measurement and Analysis Techniques for Circuit Breaker - Ahmad H.; Kiong T.S. (IEEE Computer Society, 2023)
Cost effectiveness; Electric network analysis; Electric switchgear; Failure analysis; Intelligent systems; Maintenance; Reliability analysis; Timing circuits; Actual conditions; Circuit breaker operation; Condition-based maintenance; Maintenance practices; Maintenance strategies; Measurement and analysis; Mechanical degradation; Signature analysis; Electric circuit breakers